Silicon-carbon negative electrode slurry as well as preparation method and application thereof

By adding amino alcohol compounds to the silicon carbon negative electrode slurry, the structural instability and electrolyte loss caused by volume changes in the charge and discharge process of silicon carbon negative electrode materials are solved, and the efficient liquid retention and structural stability of the battery is achieved, which extends the cycle life and improves the stability of high temperature and high pressure.

CN119786609APending Publication Date: 2025-04-08APOWER ELECTRONICS CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411985938.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The volume of silicon carbon anode material changes greatly during charging and discharging, resulting in unstable structure, difficulty in loss and retention of electrolyte, affecting the cycling performance of the battery.

Method used

Adding amino alcohol compounds to the silicon carbon negative electrode slurry will improve the liquid absorption and wetting ability of the electrode sheet and enhance the liquid storage capacity and structural stability of the battery.

Benefits of technology

It significantly improves the liquid retention ability of the negative electrode sheet and the uniform immersion of the electrolyte, extends the cycle life of the battery, and improves the high temperature and high pressure stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786609A_ABST
    Figure CN119786609A_ABST
Patent Text Reader

Abstract

The invention provides silicon-carbon negative electrode slurry as well as a preparation method and application thereof. The silicon-carbon negative electrode slurry comprises a carbon active material, a silicon active material, a conductive agent, a binder, a dispersing agent, an amino alcohol compound and a solvent. The silicon-carbon negative electrode slurry is high in uniformity, the liquid retention capacity of a negative electrode piece can be greatly improved, the negative electrode piece prepared from the silicon-carbon negative electrode slurry can also improve the high-temperature and high-pressure stability of an electrolyte in a battery, and then the high-temperature and high-pressure stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials and relates to a silicon-carbon negative electrode slurry and a preparation method and application thereof. Background Art

[0002] The capacity of the graphite anode widely used in commercial lithium batteries is about 360mAh / g, which is very close to its theoretical specific capacity (372mAh / g). It is difficult to make a breakthrough in improving the energy density of the battery on the graphite anode, so people turn their attention to silicon materials. Silicon is the second most abundant element in the earth's crust, accounting for 25.7% of the total mass of the earth's crust. It is abundant, cheap, and environmentally friendly, so the research on silicon anode materials has received widespread attention.

[0003] The structure and quality of the silicon and graphite raw materials compounded in the silicon-carbon negative electrode during the batching process are inconsistent, which will lead to uneven composition of the slurry. Among them, the stability of the silicon-carbon negative electrode slurry and the consistency of the coating film density in the conventional wet batching process are poor, affecting the consistency of the electrochemical cycle performance.

[0004] Silicon-carbon negative electrode materials undergo significant volume changes during the charge and discharge process. They expand to about three times their original volume during charge and shrink during discharge. This expansion and contraction process causes the negative electrode material to be unstable, causing electrolyte loss and difficulty in retaining it in the negative electrode. The porous structure of silicon-carbon negative electrode materials affects the adsorption and retention of electrolytes, making it difficult to retain enough electrolyte during the cycle, resulting in low capacity retention over long cycles.

[0005] CN114361390A discloses a method for preparing a silicon-carbon negative electrode slurry, a silicon-carbon negative electrode sheet and a lithium battery. The preparation method comprises the following steps: (I) mixing and stirring a negative electrode active material and a conductive agent to obtain a first mixed powder; (II) adding silicon-carbon powder and a portion of sodium carboxymethyl cellulose to the first mixed powder of step (I) and mixing them to obtain a second mixed powder, and then adding the remaining sodium carboxymethyl cellulose and a solvent to the second mixed powder to obtain an intermediate slurry; (III) adding polytetrafluoroethylene emulsion to the intermediate slurry of step (II) and mixing them evenly to obtain a silicon-carbon negative electrode slurry.

[0006] CN117695914A discloses a silicon-carbon negative electrode slurry stirring process, which makes the slurry more evenly dispersed by adjusting the slurry making process, improves the phenomenon of electrode powder falling off during the charge and discharge process of the silicon-carbon material, and improves the cycle performance of the battery. At the same time, the preparation method of the present invention adopts dry mixing of powder materials first, so that the silicon-carbon negative electrode material and the conductive agent are mixed more evenly, and the agglomeration phenomenon of the silicon-carbon material during the slurry making process is eliminated.

[0007] The silicon-carbon negative electrode slurry prepared by the above scheme has poor uniformity and low liquid retention rate after being manufactured into a battery, which affects the performance of the lithium-ion battery. Summary of the invention

[0008] The object of the present invention is to provide a silicon-carbon negative electrode slurry and a preparation method and application thereof. The silicon-carbon negative electrode slurry of the present invention has high uniformity and can greatly improve the liquid retention capacity of the negative electrode pole piece. The negative electrode pole piece made of the silicon-carbon negative electrode slurry of the present invention can also improve the high temperature and high pressure stability of the electrolyte in the battery, thereby improving the high temperature and high pressure stability of the battery.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a silicon-carbon negative electrode slurry, which includes a carbon active material, a silicon active material, a conductive agent, a binder, a dispersant, an amino alcohol compound and a solvent.

[0011] The present invention adds amino alcohol compounds to the silicon-carbon negative electrode slurry to greatly improve the liquid absorption and wetting ability of the silicon-carbon pole piece, the battery has a stronger liquid retention capacity, the electrolyte infiltration is more uniform, the battery cycle capacity is improved, and the problem of low cycle capacity retention rate of the silicon-carbon negative electrode due to drying up or loss of the electrolyte in a long cycle in the later stage is solved.

[0012] Preferably, the carbon active material comprises graphite.

[0013] Preferably, the silicon active material comprises elemental silicon.

[0014] Preferably, the conductive agent comprises conductive carbon black and / or single-walled carbon nanotubes.

[0015] Preferably, the binder comprises polyacrylate and / or styrene-butadiene rubber.

[0016] Preferably, the dispersant comprises sodium carboxymethylcellulose.

[0017] Preferably, the raw material of the amino alcohol compound is a solid amino alcohol compound.

[0018] Preferably, the amino alcohol compound includes 2-amino-2-hydroxymethyl-1,3-propanediol and / or 2-amino-2-methyl-1,3-propanediol.

[0019] The solid amino alcohol compound used in the present invention has a high melting point and good phase stability, and is evenly dispersed in the negative electrode active layer during the cycle process, which can further improve the structural stability and liquid retention capacity of the negative electrode plate.

[0020] Preferably, taking the total mass of the solute in the silicon-carbon negative electrode slurry as 100%, the mass fraction of the carbon active material is 75% to 90%, for example: 75%, 78%, 80%, 85% or 90%, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] Preferably, taking the total mass of the solute in the silicon-carbon negative electrode slurry as 100%, the mass fraction of the silicon active material is 3% to 20%, for example: 3%, 5%, 10%, 15% or 20%, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, based on the total mass of the solute in the silicon-carbon negative electrode slurry as 100%, the mass fraction of the conductive agent is 0.2% to 2.1%, for example: 0.2%, 0.5%, 1%, 1.5% or 2.1%, etc., not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0023] Preferably, based on the total mass of the solute in the silicon-carbon negative electrode slurry as 100%, the mass fraction of the binder is 2% to 7%, for example: 2%, 3%, 4%, 5%, 6% or 7%, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] Preferably, based on the total mass of the solute in the silicon-carbon negative electrode slurry as 100%, the mass fraction of the dispersant is 0.5% to 3%, for example: 0.3%, 0.5%, 1%, 2% or 3%, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] Preferably, based on the total mass of the solute in the silicon-carbon negative electrode slurry as 100%, the mass fraction of the amino alcohol compound is 0.1% to 0.5%, for example: 0.1%, 0.2%, 0.3%, 0.4% or 0.5%, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] In a second aspect, the present invention provides a method for preparing the silicon-carbon negative electrode slurry as described in the first aspect, the preparation method comprising the following steps:

[0027] (1) mixing a carbon active material, a silicon active material, a first conductive agent and a dispersant, and performing a first stirring to obtain a first mixed powder;

[0028] (2) mixing the first mixed powder with the amino alcohol compound, and performing a second stirring to obtain a second mixed powder;

[0029] (3) 40% to 60% of the first binder and 40% to 60% of the solvent are mixed with the second mixed powder, and after kneading, the second conductive agent is added, and after a third stirring, the remaining first binder and the remaining solvent are added, and after a fourth stirring, a semi-finished product slurry is obtained;

[0030] (4) The semi-finished product slurry is mixed with the second binder, and stirred for the fifth time to obtain the silicon-carbon negative electrode slurry.

[0031] The present invention prepares silicon-carbon negative electrode slurry by a specific homogenization method, which can not only improve the dispersibility of the silicon-carbon negative electrode slurry, but also avoid the destruction of the physical structure of the amino alcohol compound, thereby fully exerting the characteristics of the amino alcohol compound.

[0032] Preferably, in step (1), the first conductive agent comprises conductive carbon black.

[0033] Preferably, the revolution speed of the first stirring in step (1) is 10 rpm to 30 rpm, for example: 10 rpm, 15 rpm, 20 rpm, 25 rpm or 30 rpm, etc., not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] Preferably, the rotation speed of the first stirring in step (1) is 500rpm to 1500rpm, for example: 500rpm, 800rpm, 1000rpm, 1200rpm or 1500rpm, etc., not limited to the listed values, other values ​​not listed within the numerical range are also applicable.

[0035] Preferably, the first stirring time in step (1) is 15 min to 30 min, for example, 15 min, 18 min, 20 min, 22 min or 30 min, etc., not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0036] Preferably, the revolution speed of the second stirring in step (2) is 10 rpm to 30 rpm, for example: 10 rpm, 15 rpm, 20 rpm, 25 rpm or 30 rpm, etc., not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0037] Preferably, the rotation speed of the second stirring in step (2) is 500rpm to 1500rpm, for example: 500rpm, 800rpm, 1000rpm, 1200rpm or 1500rpm, etc., not limited to the listed values, other values ​​not listed within the numerical range are also applicable.

[0038] Preferably, the second stirring time in step (2) is 15 min to 30 min, for example, 15 min, 18 min, 20 min, 22 min or 30 min, etc., not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0039] Preferably, in step (3), the first binder comprises polyacrylate.

[0040] Preferably, in step (3), the second conductive agent comprises single-walled carbon nanotubes.

[0041] Preferably, the kneading solid content of the kneading treatment in step (3) is 60% to 70%, for example: 60%, 62%, 65%, 68% or 70%, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] Preferably, the revolution speed of the third stirring in step (3) is 15 rpm to 30 rpm, for example: 15 rpm, 18 rpm, 20 rpm, 25 rpm or 30 rpm, etc., not limited to the listed values, other values ​​not listed within the numerical range are also applicable.

[0043] Preferably, the rotation speed of the third stirring in step (3) is 1000rpm to 2000rpm, for example: 1000rpm, 1200rpm, 1500rpm, 1800rpm or 2000rpm, etc., not limited to the listed values, other values ​​not listed within the numerical range are also applicable.

[0044] Preferably, the third stirring time in step (3) is 30 min to 60 min, for example, 30 min, 35 min, 40 min, 50 min or 60 min, etc., and is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0045] Preferably, the revolution speed of the fourth stirring in step (3) is 15 rpm to 30 rpm, for example: 15 rpm, 18 rpm, 20 rpm, 25 rpm or 30 rpm, etc., not limited to the listed values, other values ​​not listed within the numerical range are also applicable.

[0046] Preferably, the rotation speed of the fourth stirring in step (3) is 1500rpm to 3000rpm, for example: 1500rpm, 1800rpm, 2000rpm, 2500rpm or 3000rpm, etc., not limited to the listed values, other values ​​not listed within the numerical range are also applicable.

[0047] Preferably, the fourth stirring time in step (3) is 60 min to 180 min, for example, 60 min, 70 min, 100 min, 150 min or 180 min, etc., and is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] Preferably, in step (4), the second adhesive comprises styrene-butadiene rubber.

[0049] Preferably, the revolution speed of the fifth stirring in step (4) is 5 rpm to 15 rpm, for example: 5 rpm, 8 rpm, 0 rpm, 12 rpm or 15 rpm, etc., not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0050] Preferably, the rotation speed of the fifth stirring in step (4) is 500rpm to 1000rpm, for example: 500rpm, 600rpm, 800rpm, 900rpm or 1000rpm, etc., not limited to the listed values, other values ​​not listed within the numerical range are also applicable.

[0051] Preferably, the fifth stirring time in step (4) is 30 min to 60 min, for example, 30 min, 35 min, 40 min, 50 min or 60 min, etc., and is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0052] In a third aspect, the present invention provides a negative electrode plate, which is prepared by coating the silicon-carbon negative electrode slurry as described in the first aspect on the surface of a copper foil.

[0053] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode sheet as described in the third aspect.

[0054] In a lithium ion battery using the negative electrode plate of the present invention, the amino alcohol compound of the negative electrode can prevent the electrolyte in the battery from decomposing under high temperature or high pressure, maintain the stability of the electrolyte, and improve the high temperature performance of the battery.

[0055] Compared with the prior art, the present invention has the following beneficial effects:

[0056] (1) The silicon-carbon negative electrode slurry of the present invention can greatly improve the liquid retention capacity of the negative electrode plate. The negative electrode plate made of the silicon-carbon negative electrode slurry of the present invention can also improve the high temperature and high pressure stability of the electrolyte in the battery, thereby improving the high temperature and high pressure stability of the battery.

[0057] (2) The stability of the silicon-carbon negative electrode slurry of the present invention is significantly improved, and the average liquid retention coefficient can reach more than 1.513 g / Ah. The number of cycles of the manufactured battery at more than 80% capacity at room temperature of 25°C can reach more than 14,200 cycles, and the number of cycles at high temperature of 45°C can reach more than 480 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 It is a stability comparison chart of the silicon-carbon negative electrode slurry prepared in Example 1 and Comparative Example 1.

[0059] Figure 2 This is the 1C cycle stability diagram of lithium cobalt oxide batteries made from silicon-carbon negative electrode slurry obtained in Example 1 and Comparative Example 1 at 25°C.

[0060] Figure 3 It is a histogram of the liquid retention coefficient capacity of the negative electrode sheets made of silicon-carbon negative electrode slurry obtained in Example 1 and Comparative Example 1.

[0061] Figure 4 This is the 1C cycle stability diagram of lithium cobalt oxide batteries made from silicon-carbon negative electrode slurry obtained in Example 1 and Comparative Example 1 at 45°C. DETAILED DESCRIPTION

[0062] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0063] Unless otherwise specified, the percentages in the embodiments and comparative examples of the present invention are all by mass percentages.

[0064] Example 1

[0065] This embodiment provides a silicon-carbon negative electrode slurry, wherein the solvent in the silicon-carbon negative electrode slurry is deionized water, and the solute includes: 83% graphite, 10% silicon, 1% conductive carbon black, 2% polyacrylate, 1.6% styrene-butadiene rubber, 2% sodium carboxymethyl cellulose, 0.05% single-walled carbon nanotubes and 0.35% 2-amino-2-hydroxymethyl-1,3-propanediol. The specific preparation method of the silicon-carbon negative electrode slurry is as follows:

[0066] (1) mixing graphite, elemental silicon powder, conductive carbon black and sodium carboxymethyl cellulose dry powder, and stirring for 20 min at a revolution speed of 20 rpm and a rotation speed of 1000 rpm to obtain a first mixed powder;

[0067] (2) mixing the first mixed powder with 2-amino-2-hydroxymethyl-1,3-propanediol, and stirring for 20 min at a revolution speed of 20 rpm and a rotation speed of 1000 rpm to obtain a second mixed powder;

[0068] (3) The second mixed powder, 50% of polyacrylate and 50% of deionized water are mixed and kneaded to a solid content of 65%. After kneading, single-walled carbon nanotubes are added, and the mixture is stirred at a speed of 20 rpm and 1500 rpm for 40 minutes. The remaining polyacrylate and deionized water are added, and the mixture is stirred at a speed of 20 rpm and 1800 rpm for 120 minutes to obtain a semi-finished slurry.

[0069] (4) Add styrene-butadiene rubber to the semi-finished product slurry, and stir for 40 minutes at a revolution speed of 10 rpm and a rotation speed of 800 rpm to obtain the silicon-carbon negative electrode slurry.

[0070] Example 2

[0071] This embodiment provides a silicon-carbon negative electrode slurry, wherein the solvent in the silicon-carbon negative electrode slurry is deionized water, and the solute includes: 85% graphite, 6% silicon, 1.9% conductive carbon black, 1% polyacrylate, 3% styrene-butadiene rubber, 2.5% sodium carboxymethyl cellulose, 0.1% single-walled carbon nanotubes and 0.5% 2-amino-2-hydroxymethyl-1,3-propanediol. The specific preparation method of the silicon-carbon negative electrode slurry is as follows:

[0072] (1) mixing graphite, elemental silicon powder, conductive carbon black and sodium carboxymethyl cellulose dry powder, and stirring at a revolution speed of 10 rpm and a rotation speed of 500 rpm for 30 min to obtain a first mixed powder;

[0073] (2) mixing the first mixed powder with 2-amino-2-methyl-1,3-propanediol, and stirring for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm to obtain a second mixed powder;

[0074] (3) The second mixed powder, 40% of polyacrylate and 60% of deionized water are mixed and kneaded to a solid content of 60%. After kneading, single-walled carbon nanotubes are added, and the mixture is stirred at a revolution speed of 30 rpm and a rotation speed of 2000 rpm for 30 minutes. The remaining polyacrylate and deionized water are added, and the mixture is stirred at a revolution speed of 30 rpm and a rotation speed of 3000 rpm for 60 minutes to obtain a semi-finished slurry;

[0075] (4) Add styrene-butadiene rubber to the semi-finished product slurry, and stir for 60 minutes at a revolution speed of 5 rpm and a rotation speed of 500 rpm to obtain the silicon-carbon negative electrode slurry.

[0076] Example 3

[0077] This embodiment provides a silicon-carbon negative electrode slurry, wherein the solvent in the silicon-carbon negative electrode slurry is deionized water, and the solute includes: 90% graphite, 5% silicon, 1.02% conductive carbon black, 1% polyacrylate, 2.3% styrene-butadiene rubber, 0.5% sodium carboxymethyl cellulose, 0.08% single-walled carbon nanotubes and 0.1% 2-amino-2-hydroxymethyl-1,3-propanediol. The specific preparation method of the silicon-carbon negative electrode slurry is as follows:

[0078] (1) mixing graphite, elemental silicon powder, conductive carbon black and sodium carboxymethyl cellulose dry powder, and stirring for 15 minutes at a revolution speed of 30 rpm and a rotation speed of 1500 rpm to obtain a first mixed powder;

[0079] (2) mixing the first mixed powder with 2-amino-2-methyl-1,3-propanediol, and stirring for 30 minutes at a revolution speed of 10 rpm and a rotation speed of 500 rpm to obtain a second mixed powder;

[0080] (3) The second mixed powder, 60% of polyacrylate and 50% of deionized water are mixed and kneaded to a solid content of 70%. After kneading, single-walled carbon nanotubes are added, and the mixture is stirred at a revolution speed of 15 rpm and a rotation speed of 1000 rpm for 60 min. The remaining polyacrylate and deionized water are added, and the mixture is stirred at a revolution speed of 15 rpm and a rotation speed of 1500 rpm for 180 min to obtain a semi-finished slurry;

[0081] (4) Add styrene-butadiene rubber to the semi-finished product slurry, and stir for 30 minutes at a revolution speed of 15 rpm and a rotation speed of 1000 rpm to obtain the silicon-carbon negative electrode slurry.

[0082] Example 4

[0083] The only difference between this embodiment and embodiment 1 is that 2-amino-2-hydroxymethyl-1,3-propanediol is replaced by 2-dimethylamino-2-methyl-1-propanol (liquid amino alcohol compound), and the other conditions and parameters are exactly the same as those in embodiment 1.

[0084] Example 5

[0085] The only difference between this embodiment and embodiment 1 is that the mass fraction of 2-amino-2-hydroxymethyl-1,3-propanediol is 0.05% (the reduced mass is filled with graphite), and the other conditions and parameters are exactly the same as those in embodiment 1.

[0086] Example 6

[0087] The only difference between this embodiment and embodiment 1 is that the mass fraction of 2-amino-2-hydroxymethyl-1,3-propanediol is 0.8% (increased mass = reduced mass of graphite), and other conditions and parameters are exactly the same as those in embodiment 1.

[0088] Comparative Example 1

[0089] The only difference between this comparative example and Example 1 is that 2-amino-2-hydroxymethyl-1,3-propanediol is not added, and other conditions and parameters are exactly the same as those in Example 1.

[0090] Slurry stability test method:

[0091] The test was conducted in a batching workshop (25°C 56% RH). A cup of slurry was taken from a container and the slurry was sealed and left to stand for 72 hours. The viscosity was tested at 0h, 2h, 4h, 8h, 12h, 24h, 48h and 72h respectively. The stability was determined based on the change in slurry viscosity measured by the viscosity tester.

[0092] Liquid retention coefficient test method:

[0093] The battery of each group of experiments in the embodiment is taken to calculate the liquid retention coefficient: liquid retention coefficient (g / Ah) = liquid retention amount / capacity.

[0094] Normal temperature cycle test method:

[0095] After placing the battery in a 25℃±3℃ environment for 120 minutes, the charge and discharge current can be determined according to the material system. Usually, it is charged at a constant current of 0.5C to the limited charging voltage, and then charged at a constant voltage until the current drops to 0.025C and the charging stops; it is left for 10 minutes, and then discharged at a current of 0.5C to 3.0V. Repeat the above steps until the battery capacity retention rate is less than 80%.

[0096] High temperature cycle test method:

[0097] After placing the battery in a 45℃±3℃ environment for 120 minutes, the charge and discharge current can be determined according to the material system. Usually, it is charged at a constant current of 0.5C to the limited charging voltage, and then charged at a constant voltage until the current drops to 0.025C and the charging stops; it is left for 10 minutes, and then discharged at a current of 0.5C to 3.0V. Repeat the above steps until the battery capacity retention rate is less than 80%.

[0098] The test results are shown in Table 1:

[0099] Table 1

[0100]

[0101]

[0102] As can be seen from Table 1, from Examples 1-6, the stability of the silicon-carbon negative electrode slurry of the present invention is significantly improved, the average liquid retention coefficient can reach more than 1.513 g / Ah, and the number of cycles of the manufactured battery at more than 80% of the capacity at room temperature of 25°C can reach more than 480 cycles, and the number of cycles at high temperature of 45°C can reach more than 220 cycles. By adjusting the amount and type of amino alcohol added, the number of cycles of the manufactured battery at more than 80% of the capacity at room temperature of 25°C can reach more than 14,200 cycles, and the number of cycles at high temperature of 45°C can reach more than 480 cycles.

[0103] By comparing Example 1 and Example 4, it can be seen that the use of a solid amino alcohol compound in the silicon-carbon negative electrode slurry of the present invention can significantly improve its performance. The solid amino alcohol compound has a high melting point and good phase stability. It is evenly dispersed in the negative electrode active layer during the cycle process, which can further improve the structural stability and liquid retention capacity of the negative electrode sheet.

[0104] By comparing Example 1 with Examples 5-6, it can be seen that in the silicon-carbon negative electrode slurry of the present invention, the addition amount of the amino alcohol compound will affect its performance. When the mass proportion of the amino alcohol compound in the solute is controlled at 0.1% to 0.5%, the performance of the silicon-carbon negative electrode slurry is better. If the proportion of the amino alcohol compound is too low, the stability of the slurry is poor, and the improvement of the liquid retention coefficient and performance is not obvious; if the proportion of the amino alcohol compound is too high, although the slurry stability and liquid retention coefficient are significantly improved, the liquid retention coefficient is too high, resulting in gas expansion of the battery during normal temperature cycle and high temperature cycle, causing the aluminum-plastic film to break and leak, resulting in the battery capacity retention rate plummeting and failure.

[0105] The stability comparison of the silicon-carbon negative electrode slurry obtained in Example 1 and Comparative Example 1 is shown in the figure below: Figure 1 As shown, the 1C cycle stability diagram of the lithium cobalt oxide battery made of the silicon-carbon negative electrode slurry prepared in Example 1 and Comparative Example 1 at 25°C is as follows Figure 2 As shown, the histogram of the liquid retention coefficient of the negative electrode sheet made of silicon-carbon negative electrode slurry obtained in Example 1 and Comparative Example 1 is as follows Figure 3 As shown, the 1C cycle stability diagram of the lithium cobalt oxide battery made of the silicon-carbon negative electrode slurry prepared in Example 1 and Comparative Example 1 at 45°C is as follows Figure 4 As shown. By comparing Example 1 with Comparative Example 1, it can be seen that the addition of amino alcohol compounds to the silicon-carbon negative electrode slurry of the present invention can greatly improve the liquid absorption and wetting ability of the silicon-carbon pole piece, the battery has a stronger liquid retention capacity, the electrolyte infiltration is more uniform, and the battery cycle capacity is improved, which solves the problem that the silicon-carbon negative electrode will not have a low cycle capacity retention rate due to the drying up or loss of the electrolyte in the later long cycle.

[0106] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A silicon-carbon negative electrode slurry, characterized in that: The silicon-carbon negative electrode slurry comprises a carbon active material, a silicon active material, a conductive agent, a binder, a dispersant, an amino alcohol compound and a solvent.

2. The silicon-carbon negative electrode slurry according to claim 1, characterized in that: The carbon active material includes graphite; Preferably, the silicon active material comprises elemental silicon; Preferably, the conductive agent comprises conductive carbon black and / or single-walled carbon nanotubes; Preferably, the binder comprises polyacrylate and / or styrene-butadiene rubber; Preferably, the dispersant comprises sodium carboxymethyl cellulose; Preferably, the raw material of the amino alcohol compound is a solid amino alcohol compound; Preferably, the amino alcohol compound includes 2-amino-2-hydroxymethyl-1,3-propanediol and / or 2-amino-2-methyl-1,3-propanediol.

3. The silicon-carbon negative electrode slurry according to claim 1, characterized in that: Taking the total mass of the solute in the silicon-carbon negative electrode slurry as 100%, the mass fraction of the carbon active material is 75% to 90%; Preferably, based on the total mass of the solute in the silicon-carbon negative electrode slurry being 100%, the mass fraction of the silicon active material is 3% to 20%; Preferably, based on the total mass of the solute in the silicon-carbon negative electrode slurry being 100%, the mass fraction of the conductive agent is 0.2% to 2.1%; Preferably, based on the total mass of the solute in the silicon-carbon negative electrode slurry being 100%, the mass fraction of the binder is 2% to 7%; Preferably, based on the total mass of the solute in the silicon-carbon negative electrode slurry being 100%, the mass fraction of the dispersant is 0.5% to 3%; Preferably, based on the total mass of the solute in the silicon-carbon negative electrode slurry being 100%, the mass fraction of the amino alcohol compound is 0.1% to 0.5%.

4. A method for preparing the silicon-carbon negative electrode slurry according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing a carbon active material, a silicon active material, a first conductive agent and a dispersant, and performing a first stirring to obtain a first mixed powder; (2) mixing the first mixed powder with the amino alcohol compound, and performing a second stirring to obtain a second mixed powder; (3) 40% to 60% of the first binder and 40% to 60% of the solvent are mixed with the second mixed powder, and after kneading, the second conductive agent is added, and after a third stirring, the remaining first binder and the remaining solvent are added, and after a fourth stirring, a semi-finished product slurry is obtained; (4) The semi-finished product slurry is mixed with the second binder, and stirred for the fifth time to obtain the silicon-carbon negative electrode slurry.

5. The preparation method according to claim 4, characterized in that: Step (1) The first conductive agent includes conductive carbon black; Preferably, the revolution speed of the first stirring in step (1) is 10 rpm to 30 rpm; Preferably, the rotation speed of the first stirring in step (1) is 500 rpm to 1500 rpm; Preferably, the first stirring time in step (1) is 15 min to 30 min.

6. The preparation method according to claim 4 or 5, characterized in that: Step (2) the second stirring revolution speed is 10 rpm to 30 rpm; Preferably, the rotation speed of the second stirring in step (2) is 500 rpm to 1500 rpm; Preferably, the second stirring time in step (2) is 15 min to 30 min.

7. The preparation method according to any one of claims 4 to 6, characterized in that: Step (3) the first binder comprises polyacrylate; Preferably, in step (3), the second conductive agent comprises single-walled carbon nanotubes; Preferably, the kneading solid content of the kneading treatment in step (3) is 60% to 70%; Preferably, the revolution speed of the third stirring in step (3) is 15 rpm to 30 rpm; Preferably, the rotation speed of the third stirring in step (3) is 1000 rpm to 2000 rpm; Preferably, the third stirring time in step (3) is 30 min to 60 min; Preferably, the revolution speed of the fourth stirring in step (3) is 15 rpm to 30 rpm; Preferably, the rotation speed of the fourth stirring in step (3) is 1500 rpm to 3000 rpm; Preferably, the fourth stirring time in step (3) is 60 min to 180 min.

8. The preparation method according to any one of claims 4 to 7, characterized in that: Step (4) the second adhesive comprises styrene-butadiene rubber; Preferably, the revolution speed of the fifth stirring in step (4) is 5 rpm to 15 rpm; Preferably, the rotation speed of the fifth stirring in step (4) is 500 rpm to 1000 rpm; Preferably, the fifth stirring time in step (4) is 30 min to 60 min.

9. A negative electrode plate, characterized in that: The negative electrode plate is prepared by coating the silicon-carbon negative electrode slurry as described in any one of claims 1 to 3 on the surface of a copper foil.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Lithium ion battery anode material, negative pole piece as well as preparation method and application of negative pole piece

    CN106784662A

  • Preparation method of silicon-carbon negative electrode slurry, silicon-carbon negative electrode plate and lithium battery

    CN114361390A

  • Negative electrode slurry and preparation method thereof, negative electrode plate and lithium ion battery

    CN115911269A